DeepVessel: Retinal Vessel Segmentation via Deep Learning and Conditional Random Field - Fu, Huazhu; Xu, Yanwu; Lin, Steve; Wong, Damon Wing Kee; Liu, Jiang (Medical Image Computing and Computer Assisted Intervention (MICCAI), 2016)
Retinal vessel segmentation is a fundamental step for various ocular imaging applications. In this paper, we formulate the retinal vessel segmentation problem as a boundary detection task and solve it using a novel deep learning architecture. Our method is based on two key ideas: (1) applying a multi-scale and multi-level Convolutional Neural Network (CNN) with a side-output layer to learn a rich hierarchical representation, and (2) utilizing a Conditional Random Field (CRF) to model the long-range interactions between pixels. We combine the CNN and CRF layers into an integrated deep network called DeepVessel. Our experiments show that the DeepVessel system achieves state-of-the-art retinal vessel segmentation performance on the DRIVE, STARE, and CHASE_DB1 datasets with an efficient running time.